DRUMMOND - UMA REFERÊNCIA CONSTANTE NA MODERNA POESIA AFRICANA DE LÍNGUA PORTUGUESA - Carmen Lucia Tindo (TRF2, 2019)
Carlos Drummond de Andrade was and continues to be a striking reference for Portuguese-speaking African poetry. During the struggles for liberation in Angola and Mozambique and in the following years, the poems of Sentimento do mundo, José and A Rosa do povo became paradigms of generations of poets committed to the social, denouncing the "fascist night" among the Luis Carlos Patraquim, Eduardo White, Paula Tavares and others.